Taxonomy of the order Bunyavirales: second update 2018 - Maes, Piet; Adkins, Scott; Alkhovsky, Sergey V.; Avšič-Županc, Tatjana; Ballinger, Matthew J.; Bente, Dennis A.; Beer, Martin; Bergeron, Éric; Blair, Carol D.; Briese, Thomas; Buchmeier, Michael J.; Burt, Felicity J.; et al. (ARCHIVES OF VIROLOGY, 2019)
In October 2018, the order Bunyavirales was amended by inclusion of the family Arenaviridae , abolishment of three families, creation of three new families, 19 new genera, and 14 new species, and renaming of three genera and 22 species. This article presents the updated taxonomy of the order Bunyavirales as now accepted by the International Committee on Taxonomy of Viruses (ICTV).